Study of 100 Cases of Strokes for Infarction and Hemorrhage in Swat (Medical Forum Monthly, 2024)
Objectives:The main objective of this study conducted was to compare the incidence of cerebral infarction and hemorrhage in one hundred patients of stroke over a time span of one year in swat.Study Design:Cross sectional studyPlace and Duration of Study: This study was conducted at the Department of Medicine, Saidu Teaching Hospital Saidu Sharif Swat from January 2015 till January 2016.Materials and Methods:Hundred patients were selected for this study and their data recorded including history of smoking or any medical disorder, especially Diabetes mellitus, previous cerebrovascular accident, transient ischemic attacks, history of previous cardiac events such as coronary artery disease, angina, Myocardial infarction. Vital monitoring was performed at the time of presentation and 24 hourly thereafter.Results: Among selected patients 62% were males and 38% were Females.18% patients were in age group 51- 60 year, 32% patients were in age group 61- 70 year, 24% patients were in age group 71- 80 year, 78% of patients were having cerebral infarction, while cerebral hemorrhage was found in 22% of patient.Hypertension was the most common risk factor among these stroke patients. Average blood pressure was 160 / 100.Conclusions:Common cause of stroke is cerebral infarction while the leading risk factor found is Hypertension in patients with stroke.